PREVALENCE OF ERECTILE DYSFUNCTION AFTER PELVIC RADIOTHERAPY - ANWER , RA; BASHIR , A; SHER , HF; MANAN , A; AMMARA , A (Biological and Clinical Sciences Research Journal, 2024)
Erectile dysfunction (ED) is a common complication among male cancer survivors undergoing pelvic radiotherapy, significantly impacting their quality of life. Despite its high prevalence globally, data on ED among Pakistani cancer survivors remain limited. Objective: To determine the prevalence, severity, and associated risk factors of ED among male patients undergoing pelvic radiotherapy at Nishtar Medical University and Hospital, Multan. Methods: This prospective observational study included 50 male patients aged 50–85 years undergoing pelvic radiotherapy for malignancies. Baseline and six-month follow-up assessments of erectile function were conducted using the International Index of Erectile Function (IIEF-5) questionnaire. Factors associated with ED, including age, comorbidities, and treatment parameters, were analyzed using SPSS version 26.Results: The prevalence of ED six months post-radiotherapy was 61%. Advanced age (≥65 years) and diabetes were significant risk factors, with 71.4% and 88.9% of patients, respectively, developing ED. Moderate and severe ED accounted for 42.9% and 35.7% of cases, respectively. Cultural stigma and limited healthcare resources were additional barriers to managing ED in the Pakistani context. Conclusion: ED is highly prevalent among male patients undergoing pelvic radiotherapy, with advanced age and diabetes being significant contributors. These findings underscore the need for routine ED screening, culturally sensitive counseling, and targeted interventions to improve the quality of life for cancer survivors in Pakistan.